The effects of body composition and selected functional and anthropometric measures on the acquisition of beginning water competencies among adult males - Stallman, R. K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Conventional wisdom suggests that persons with greater buoyancy succeed more easily in learning to swim. Little evidence is available about the acquisition of beginning water competencies as related to body composition, functional buoyancy and floating angle. The aims of this study were to examine the effects of body composition and selected functional and anthropometric measures on the acquisition of these beginning swimming competencies. One hundred and twenty men ages 18 to 26 participated. The instructional program consisted of 10 one-hour sessions. The candidates were categorized as floating at a) less than 300, b) between 300 and 600, c) more than 600, d) vertically or not at all. Body composition was determined by classic underwater weighing. Functional buoyancy was defined as density with full inspiration, uncorrected. Floating angle was determined against a backdrop marked at 300 and 600. Thirty two measures of skin fold fat, girths, and breadths were recorded. Functional variables were, underwater weight, body density, % fat, lean body mass, vital capacity, floating angle, ankle drag, functional buoyancy with maximum inspiration and functional buoyancy with maximum expiration. Statistical analysis consisted of product moment, bi-serial and phi coefficient correlation. The instructional program included 16 test items. Anthropometric variables correlated poorly with buoyancy, floating angle and final success. Floating angle correlated poorly, with final success. Functional buoyancy correlated moderately with final success. Neither floating angle nor functional buoyancy correlated sufficiently with final success to warrant major adaptations to teaching. Success among the poorest floaters was lower than others. Persons of deep floating angle or low buoyancy may require a longer period of instruction.